Apprentissages ducoachen situation de travail : quelle plus-value en contexte multiculturel libanais ? - Mirna Hage; Patricia Rached; Yvette Gharib (Éducation et Socialisation)
The aim of this qualitative case study was to depict the coaching experience of a coach and what he learned when he accompanied five school principals for one year, within the Lebanese multicultural context. The socio-constructivist theory with its interpretive paradigm constituted the theoretical framework. Throughout one academic year, data was collected via three semi-structured interviews with the coach and the analysis of the content of his logbook. The findings highlighted the contributions of coaching in terms of the relationship with others in addition to the importance of operating in a resourceful environment. As a result, the coach’s field involvement led to mobilizing learning strategies and developing professional behaviors in the workplace.